Genome-wide identification and expression analysis of bHLH gene family revealed their potential roles in abiotic stress response, anthocyanin biosynthesis and trichome formation in Glycyrrhiza uralensis - Guohua Ding; Yanping Shi; Kerui Xie; Hongbin Li; Guanghui Xiao (Frontiers in Plant Science)
IntroductionLicorice stands out as an exceptional medicinal resource with a long history of application, attributed to its substantial pharmacological potential. The basic helix-loop-helix (bHLH) transcription factors (TFs) gene family, being the second-largest in plants, is vital for plant development and adapting to environmental shifts. Despite this, the comprehensive characteristics of licorice bHLH gene family are not well-documented.ResultsIn this study, a detailed and thorough genome-wide identification and expression analysis of Glycyrrhiza uralensis bHLH gene family was carried out, resulting in the identification of 139 licorice bHLH members. Our duplication analysis highlighted the significant contribution of segmental duplications to the expansion of G. uralensis bHLH genes, with GubHLH genes experiencing negative selection throughout evolution. It was discovered that GubHLH64 and GubHLH38 could be importantly linked to the licorice trichome initiation and anthocyanin biosynthesis and GubHLH64 was also involved in the abiotic stress response. Additionally, certain subfamily III (d+e) GubHLH members could be implicated in the licorice drought response. GubHLH108, GubHLH109, and GubHLH116 were suggested to form a tightly related cluster, initiating transcriptional responses via JA signaling pathway.DiscussionIn summary, our findings furnish a foundational understanding for future investigations of GubHLH gene functions and regulation mechanisms, shedding light on the potential applications of licorice in medicine and agriculture.